Threshold Response to Extreme Drought Shifts Inter-Tree Growth Dominance in Pinus sylvestris - Ovenden, Thomas S.; Perks, Mike P.; Clarke, Toni-Kim; Mencuccini, Maurizio; Jump, Alistair S. (Frontiers in Forests and Global Change, 2021)
Many studies quantify short-term drought impact on tree growth relative to pre-drought growth averages. However, fewer studies examine the extent to which droughts of differing severity differentially impact tree growth or shape stand dynamics. Focusing on three droughts in high and low density stands of Pinus sylvestris in Scotland, we calculated pre-drought growth averages using climatically standardised antecedent growth years to assess tree level drought and post-drought growth performance as percentage growth change (PGC). We then used mixed-effects models to understand how droughts of differing severity impact tree growth and calculated indices of growth dominance (Gd), size inequality (Si) and size asymmetry (Sa) to detect changes in stand structure. Mixed-effects model results indicate that the magnitude and duration of the growth reduction during and following the more extreme drought was significantly larger compared to less severe droughts, for which we found limited evidence of drought impact. While no changes in Si or Sa were noted following any drought, we found evidence of a difference in Gd after the most extreme drought in both stand densities indicative of a threshold response, with smaller trees contributing proportionally more to stand growth relative to their size. Under less severe droughts, inter-tree variability may have partially buffered against stand-level growth change, however a small increase in drought severity was associated with a significant reduction in average tree growth, an increase in the number of trees growing at > 2SD below pre-drought levels and a shift in Gd towards smaller trees, indicating that a drought severity threshold in P. sylvestris may have been exceeded.